Selection of Specialty for Post Graduation by Medical Doctors: A Need for Career Conselor in Medical Institutions - MUHAMMAD ASLAM, AYESHA SHAUKAT, ANDLEEB KHANUM (Journal of Fatima Jinnah Medical University, 2018)
Introduction: The post graduate speciality selected by a medical doctor plays an important role in the production of satisfied, content and enthusiastic medical specialists. Many young doctors do not seem to be very satisfied with their jobs and show a lack of interest in their fields of specialization so we decided to carry out a study to know the factors considered by these young doctors for opting for a particular speciality. We also wanted to know the level of satisfaction among these doctors perusing their respective fields of post graduation. Moreover, there is another alarming fact that as a result of open merit in medical colleges, the number of female doctors is increasing per anum. The lady doctors are more concentrated in specialties like gynae and obstetrics, pediatrics, pathology etc and show no interests in fields like neurosurgery, urology etc.Role of career conselor is clearly lacking in the medical institutions. Aims and Objectives: To evaluate level of satisfaction among young postgraduate trainees. To study the over saturation of certain specialties. To evaluate the need for a career Conselor in medical institutions . Material and Methods: A cross sectional questionnaire based survey was carried out among 136 female and 136 male post graduate trainees working in different specialties in Ganga Ram Hospital, Lahore General Hospital and Children Hospital. RESULTS:A total of 272 post graduate trainees responded to the our questionnaire based survey. Reasons for selecting particular speciality included their own wishes (69.8%)Future private practice was among the second most popular reasons (16.5%)Family pressure (10.6%) and work life balance ( 10.2%) were also among common reasons .Peer pressure , easy job , opportunity to settle abroad, double job opportunity were also reasons considered by some trainees. Majority of female postgraduate were working in gynae and obstetrics , pediatrics , pathology . Vice versa there was no male post graduate in gynae and obstetrics.44% of trainees were moderately satisfied .36.7% of trainees were well satisfied . 19 % were dissatisfied with their chosen fields of specialization. No post graduate was guided by a career conselor while chosing these specialties. Conclusion: There is gender based saturation in many fields of medical specialization that may eventually lead to lack of specialists in less popular fields. Though the medical doctors have chosen their respective fields of specialization themselves yet they are not very happy with their selection. This indicates that they probably were not aware of their aptitude and could have done better if they were guide by a career conselor.